Voyaging Through Uncharted Territories: A Phenomenological Study of Elementary Education Amidst the New Normal - Magbanua, Yehlen S. (Future Science / FSH-PH Publications, 2024)
As the world slowly recovers from the COVID-19 pandemic, it is clear that we will not be returning to the world we once knew. Instead, we are adapting to a